2020
DOI: 10.1103/physrevd.101.023006
|View full text |Cite
|
Sign up to set email alerts
|

Velocity substructure from Gaia and direct searches for dark matter

Abstract: Data from the Gaia satellite show that the solar neighbourhood of the Milky Way's stellar halo is imprinted with substructure from several accretion events. Evidence of these events is found in "the Shards", stars clustering with high significance in both action space and metallicity. Stars in the Shards share a common origin, likely as ancient satellite galaxies of the Milky Way, so will be embedded in dark matter (DM) counterparts. These "Dark Shards" contain two substantial streams (S1 and S2), as well as s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
95
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 205 publications
(246 reference statements)
1
95
0
1
Order By: Relevance
“…In Table I, we list v mp , t c , and b for possible local DM components we consider throughout this work: the SHM, Gaia halo and Sausage [16], and possible DM streams associated with Nyx [18], S1, S2a, and S2b [22] stellar streams. Note that we use the values of the stellar streams as benchmarks for the potential dark matter distributions associated with Nyx, S1, S2a, and S2b.…”
Section: B Astrophysics Setupmentioning
confidence: 99%
See 3 more Smart Citations
“…In Table I, we list v mp , t c , and b for possible local DM components we consider throughout this work: the SHM, Gaia halo and Sausage [16], and possible DM streams associated with Nyx [18], S1, S2a, and S2b [22] stellar streams. Note that we use the values of the stellar streams as benchmarks for the potential dark matter distributions associated with Nyx, S1, S2a, and S2b.…”
Section: B Astrophysics Setupmentioning
confidence: 99%
“…The standard halo model (SHM), in which the velocities of the DM particles follow an isotropic Maxwellian distribution, has commonly been used in the computation of DM direct detection rates. Recent work, however, has shown that the Milky Way's history has been punctuated by mergers with dwarf galaxies, which resulted in a rich variety of stellar substructure beyond the traditional halo and disk, such as the debris flow of the Gaia Sausage (also called Enceladus) [16,17], the Nyx stream [18,19], or the so-called "shards," the S1, S2a, and S2b streams [20][21][22]. 1 Since dwarf galaxies also contain DM, these mergers could also result in associated dark matter substructure within our galaxy, beyond that of what pertains to the SHM.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another promising avenue to look for interesting signatures of DM substructure are axion searches and directional detection experiments as discussed in refs. [37][38][39]. The main drawback of the aforementioned analyses is the underlying assumption of a near perfect stellar-DM velocity correlation.…”
Section: Introductionmentioning
confidence: 99%